(untitled) (Chest & Heart Journal, 2023)
Background: Bronchiectasis is a disease state defined by irreducible dilations of the airways. If the changes occur in diseases other than cystic fibrosis they are termed non-CF bronchiectasis. Long-term therapy with nebulized gentamicin can eradicate the infection or reduce the bacterial load, decrease the risk of subsequent infections and improve the quality of life in patients with non-CF bronchiectasis with a minimal risk of side effect. Aims: The aim of this study was to find out the outcome of long term nebulization of gentamicin on lung function and respiratory health status among non-CF bronchiectasis. Materials & Methods: This prospective randomized controlled trial (RCT) was conducted at the Department of Respiratory Medicine in National Institute of Diseases of the Chest and Hospital from April 2020 to March 2021 in collaboration with the Department of Pathology, Radiology and Respiratory Laboratory. A total of 50 Non-CF Bronchiectasis patients were equally divided into 2 groups, gentamicin group and placebo group. All data were analyzed by using computer based SPSS-23(Statistical Packages for Social Sciences). P value of less than 0.05 was considered as significant. Results: Out of 50 patients with non-CFbronchiectasis, mean age was found 50.0±11.0 years in gentamicin group and 46.3±11.4 years in placebo group.Eighteen (72.0%) patients were male in group A and Sixteen(64.0%) in group B. Male to female ratio was 2.6:1 in group A and 1.8:1 in group B. Age, sex, occupational status, co-morbidities and BMI, were not statistically significant (p>0.05) between two groups. Following gentamicin therapy,SGRQ (36.0±10.2 vs 41.8±7.9) and 24 hour sputum volume (5.2±3.9 vs 7.8±2.5) was significantly decreased in gentamicin group than placebo group (p= 0.001). After gentamicin therapy, mean mMRC was not statistically significant between two groups (p=0.267). After therapy FEV1 was significantly increased in gentamicin group than placebo group (42.5±9.4% vs 37.4±6.0, p=0.001). Conclusion. We observed that gentamicin could significantly improve SGRQ and FACED score and reduce sputum volume compared to placebo. After therapy FEV1 was significantly increased in gentamicin group than placebo group. Nebulized gentamicin may be used as an effective suppressive antibiotic therapy in these patient group. Chest Heart J. 2021; 45(2) : 93-98